Thrombospondin 1 in Metabolic Diseases - Gutierrez, Linda S.; Gutierrez, Jovita (Frontiers in Endocrinology, 2021)
The thrombospondin family is a group of five multifunctional glycoproteins, whose best-studied member is thrombospondin 1 (TSP1). This matricellular protein is a potent antiangiogenic agent that inhibits endothelial migration and proliferation, and induces endothelial apoptosis. Studies have demonstrated a regulatory role of TSP1 in cell migration and in activation of the latent transforming growth factor beta 1 (TGFβ1). These functions of TSP1 clearly translate into its broad modulation of immune processes. Further, imbalances in immune regulation have been increasingly linked to pathological conditions such as obesity and diabetes mellitus. While most studies in the past have focused on the role of TSP1 in cancer and inflammation, recently published data have revealed new insights about the role of TSP1 in physiological and metabolic disorders. Here, we highlight recent findings that associate TSP1 and its receptors to obesity, diabetes, and cardiovascular diseases. TSP1 regulates nitric oxide, activates latent TGFβ1, and interacts with receptors CD36 and CD47, to play an important role in cell metabolism. Thus, TSP1 may be considered a potential therapeutic target for metabolic diseases.